Life Satisfaction and Income Comparison Effects in Turkey - DUMLUDAĞ, DEVRİM (SPRINGER, 2013)
This paper evaluates the relative impact of different types of benchmarks such as internal and external comparisons on subjective well-being in Turkey. There are few studies on life satisfaction for Turkey and they mostly focus on the impact of socio-demographic effects on subjective well-being. The main purpose of this paper is to investigate how reference group's self-reported life satisfaction is related to the level of consumption; as well as the level of internal and external comparisons and other socio-economic factors. The paper relies on the Life in Transition Survey (EBRD 2011), a survey conducted in late 2010 jointly by the European Bank for Reconstruction and Development and the World Bank. The survey includes 1,003 observations for Turkey. The emphasis of the paper is based on the concept of income comparisons-both to others in the relevant reference group and to oneself in the past (evaluation) and future (expectation). The main findings are; in addition to household consumption, internal and external comparisons have significant impact on life satisfaction. The impact of comparisons is asymmetric: in most cases under-performing one's benchmark has a greater effect than out-performing it.
Keywords: Life satisfaction; Turkey; Ordered logit model; Relative income; HAPPINESS